Planejamento empresarial sucessório: holding familiar versus inventário – um novo olhar sobre a longevidade do patrimônio nas empresas familiares - Poderoso, Marluany Sales Guimarães (2024)
Nowadays, one of the great challenges of the Brazilian business community is maintaining the company in a hostile business environment, whatever the chosen corporate type. The receipt of putting personal assets at risk makes the entrepreneur seek safer alternatives for the allocation of investments and, in this scenario, all these challenges are potentialized in family businesses. The option of setting up a Family Holding, to guide succession planning, by replacing the inventory process, can be a path when it comes to companies of family origin. Thus, the present work aims to identify precepts and values fundamental to the relationships protected in family businesses through the analysis of the constitutional guarantees of hereditary succession, as well as to verify the main challenges of the manager to ensure the permanence of the patrimony using more comprehensive legal treatment procedures and guidelines, including in relation to leadership burdens in family businesses. The methodology used, applied in the review of bibliographical and documentary research to promote the analysis of the proposed subject and support in the field of corporate constitutional law, as well as the vast specialized literature in articles, periodicals, theses, news and legal documents incorporated to the theme. Finally, it appears that a company, of the Family Holding type, can be the target of illicit conduct and fraudulent practices by its manager, bringing insecurity to the heirs, which is why reconciling business principles and objectives with the protection of fundamental human rights, through da The application of the compliance program in family holdings can be an alternative to bring greater security regarding the assets of each partner, heirs and relatives.